2005
DOI: 10.1016/j.jacc.2004.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic ventricular arrhythmia arising from the mitral annulus

Abstract: Mitral annular VT/PVC is a rare but distinct subgroup of IVT/PVC. MAVT/PVC origin could be determined by ECG analysis. The AL and PS sites of the MA were preferential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(40 citation statements)
references
References 23 publications
6
33
0
1
Order By: Relevance
“…The QRS morphology in our patient was similar to those reported by Tada et al3 for posterior-mitral annular VT/PVCs. In their series, among the 19 VT/PVCs originating from the annulus, two originated from the posterior mitral annulus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The QRS morphology in our patient was similar to those reported by Tada et al3 for posterior-mitral annular VT/PVCs. In their series, among the 19 VT/PVCs originating from the annulus, two originated from the posterior mitral annulus.…”
Section: Discussionsupporting
confidence: 90%
“…Tada et al3 reported that 5% of IVT/PVCs originate from the mitral annulus. They studied the prevalence, ECG characteristics, and preferential site of tachycardia origin within the mitral annulus and the efficacy of RFCA for IVT of this kind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). Als weitere eigene Entität innerhalb der linksventrikulären Tachykardien wurde jüngst ein Tachykardie-Ursprung in enger anatomischer Beziehung zum Mitralklappenring beschrieben [31].…”
Section: Idiopathische Rechts-und Linksventrikuläre Tachykardieunclassified
“…In recent years, radiofrequency catheter ablation (RFCA) has proven to be a safe and successful therapy for the arrhythmias [2-5]. PVCs mainly originate from the right ventricular outflow tract, with a small part of them originating from the left ventricular outflow tract, mitral and tricuspid valve annulus [6-11]. However, idiopathic PVCs that originated from the left ventricular septum, not involving the left anterior or posterior fascicle, have also been observed.…”
Section: Introductionmentioning
confidence: 99%